ANALYSIS OF TOTAL FLAVONOID LEVELS OF ETHANOL EXTRACT (Cinnamon (Cinnamomum burmanii Blume) LEAVES WITH UV-VIS SPECTROPHOTOMETRY METHOD - P, Darmayuda I P; G, Suardana I; A. A, Bawa Putra (Jurnal Ilmu Pendidikan Indonesia, 2021)
Cinnamon plants (Cinnamomum burmani Blume), including plants that have medicinal properties for diabetes mellitus because they contain flavonoid compounds. This study aimed to determine the total flavonoids content of the ethanol extract of cinnamon leaf ethanol extract using UV-Vis spectrophotometry method. The ethanol extract of Cinnamon leaf was obtained by maceration using ethanol as a solvent.The qualitative analysisÂ usedÂ FeCl3byÂ formingÂ yellowish greenÂ complex.Â TheÂ determinationÂ ofÂ totalÂ flavonoidsÂ contentÂ isÂ conducted basedon AlCl3methodÂ withÂ totalÂ flavonoidseÂ xpressedÂ inÂ QEÂ (QuercetinÂ equivalent) atÂ theÂ maximumÂ wavelengthÂ ofÂ 435Â nm.Â The result showed that the average content of flavonoid total is 19.544 mg QE/g extract.